2022
DOI: 10.1093/ajcn/nqac280
|View full text |Cite
|
Sign up to set email alerts
|

Chronic aflatoxin exposure during pregnancy is associated with lower fetal growth trajectories: a prospective cohort from the Butajira Nutrition, Mental Health, and Pregnancy (BUNMAP) Study in rural Ethiopia

Abstract: Background Aflatoxins are toxic secondary metabolites produced by Aspergillus fungi, which are ubiquitously present in the food supplies of low- and middle-income countries. Studies of maternal aflatoxin exposure and fetal outcomes are mainly focused on size at birth and the effect on intrauterine fetal growth has not been assessed. Objectives In the present study, we examine the association between chronic aflatoxin exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A study from Ethiopia found an association between chronic maternal AF exposure and lower fetal growth trajectories using fetal biometry from ultrasound estimates. However, the same study did not find an association of AF exposure with birth anthropometry (56). A systematic review of studies that evaluated mycotoxin exposure and infant growth also found inconsistent results (28).…”
Section: Discussionmentioning
confidence: 96%
“…A study from Ethiopia found an association between chronic maternal AF exposure and lower fetal growth trajectories using fetal biometry from ultrasound estimates. However, the same study did not find an association of AF exposure with birth anthropometry (56). A systematic review of studies that evaluated mycotoxin exposure and infant growth also found inconsistent results (28).…”
Section: Discussionmentioning
confidence: 96%
“…Children are vulnerable due to their lower body mass, higher metabolic rate and developing detoxification system [107] (Peraica, Richter and Rašić, 2014). A study in Ethiopia reported a high occurrence of long-tern maternal aflatoxin exposure and an associated risk of poorer fetal growth trajectories [111] ( Tesfamariam et al, 2022). In Burkina Faso, limited biological and toxicological food contamination data are available [101] (Kpoda et al, 2022), and regulations or legislation concerning mycotoxins are often not implemented [115,116] (FAO, 2003; Warth et al, 2012).…”
Section: Mycotoxinsmentioning
confidence: 99%
“…In another prospective cohort study conducted by Tesfamariam et al, the association between chronic aflatoxin exposure during pregnancy and fetal growth trajectories was examined. In this study, aflatoxin was found in 86.6% of maternal blood samples ( n , 492), and the aflatoxin-exposed group showed a significantly lower change in fetal weight-for-gestational-age centile change over time than the unexposed group [ 38 ].…”
Section: Introductionmentioning
confidence: 99%